Physical properties of the (K0·44Na0·52Li0.04)0.97La0·01Nb0·9Ta0·1O3 ceramic with coexisting tetragonal and orthorhombic monocrystalline grains at room temperature. Issue 9 (1st May 2021) - Fuentes, J.; Portelles, J.; Durruthy Rodríguez, M.D.; Ostos, C.; Gervacio Arciniega, J.J.; Bedolla Valdez, Z.I.; Siqueiros, J.M.; Raymond Herrera, O.
Abstract: A structural and physical properties study on ferroelectric (K0·44 Na0·52 Li0.04 )0.97 La0·01 Nb0·9 Ta0·1 O3 ceramics with monocrystalline grains of orthorhombic (O) and tetragonal (T) perovskite phases coexisting at room temperature (RT) is presented. Different sintering temperatures were evaluated. XRD analysis demonstrates high crystalline quality of both phases with volume fractions depending of the sintering temperature. SEM shows grain facets and morphologies of both phases in all samples. Raman analysis confirms the dopant incorporation and the coexistence of both phases. The contributions of each phase in the dielectric response are deconvoluted using the frequency-temperature dielectric analysis. The orthorhombic-to-tetragonal (TO-T ) and tetragonal-to-cubic (TT-C ) phase transition temperatures shift 100 °C below those reported for pure-KNN in all samples, as consequence of the Li, La, and Ta doping combination. Li doping promotes T-phase grain growth and decreases TO-T below RT. La incorporation promotes the O-phase grain growth and decreases TO-T and TT-C . The optimal sintering temperature is 1180 °C with 50-50 volume fractions of T-O phases. Piezoresponse studies show a complex 180°-domain structure. Graphical abstract: Image 1 Highlights: Lead free Li/La doped KNNTa ceramic is constituted by coexisting tetragonal and orthorhombic structured grains. Li doping promotes tetragonal grain growth and La incorporation promotes the orthorhombic grain growth. Li and La combination shifts the FE-FE transition below room temperature. The coexistence of two phases provides better room temperature functionality for applications.